2017
DOI: 10.1007/s12544-017-0256-6
|View full text |Cite
|
Sign up to set email alerts
|

Crowd logistics: an opportunity for more sustainable urban freight transport?

Abstract: Purpose Passenger car occupancy has been falling for years. Partly empty vehicles on our road networks decrease passenger transport sustainability but also contain an opportunity for freight transport. Within Crowd logistics (CL), delivery operations are carried out by using passengers' excess capacity on journeys that are already taking place, resulting in economic, social and environmental benefits. Existing CL initiatives show, however, that there are important differences between concepts in terms of susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
157
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 26 publications
2
157
0
2
Order By: Relevance
“…Based on the OIPT view, a platform's informative support can be treated as a type of information processing mechanism. Particularly, platforms offer customers informative service that helps them issue their logistics service requests to drivers [27]. Platforms then categorize such information according to the characteristics of service requests and construct a multidimensional database.…”
Section: The Mediating Effect Of Logistics Resource-demand Matchmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the OIPT view, a platform's informative support can be treated as a type of information processing mechanism. Particularly, platforms offer customers informative service that helps them issue their logistics service requests to drivers [27]. Platforms then categorize such information according to the characteristics of service requests and construct a multidimensional database.…”
Section: The Mediating Effect Of Logistics Resource-demand Matchmentioning
confidence: 99%
“…First, a contribution of our study is that we construct a theoretical framework for the platform's informative support-logistics performance relationship based on organization information processing theory. By conducting case studies, scholars pointed out that crowd logistics platforms assist drivers in providing customers with faster and more flexible logistics services and help save costs [27,28]. However, few studies could explain how crowd logistics platforms contribute to logistics performance.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research studies [8][9][10][11][12] have confirmed that the quality of transport infrastructure is considered a crucial element which makes decisions about the foreign investment allocation very often. The offered quality of transport network connectivity is considerably related to services provided within transport sector [4].The main task of transport is to satisfy the customers' requirements for quality, flexible, fast, and safe transportation of passengers and cargo [1,3]. Quality is differently perceived from the transport user [12], transport services provider, or transport organizer point of view, but also from the society-wide point of view.…”
mentioning
confidence: 99%
“…Customers' needs and expectations are monitored by establishing procedures in accordance with the Regulation (EC) No 1371/2007 of the European Parliament and of the Council of 23 October 2007 on rail passengers' rights and obligations [14][15][16].Based on the previous research studies [17][18][19][20][21], it can be declared that one of the fundamentals of providing transport services is to offer travel opportunities by designing transport network connectivity among individual transport lines, i.e., assessing the transport connectivity and travel opportunities themselves. Often, after implementing the new timetable in rail transport, particularly the train schedule diagram, discussions are going on about whether it is better or worse than in the previous period, while assessing is approached solely subjectively [3,4,17].The availability of destinations and the frequency of connections are also important criteria for passengers in relation to public transport [3,13]. The key task of transport services is, therefore, to provide ample travel opportunities accordingly, whilst that of the infrastructure is to create the opportunity to provide a comprehensive service within a given state, specific geographical agglomeration, or area of interest [22][23][24].…”
mentioning
confidence: 99%